Efficacy of the anti-seizure medications in acute symptomatic neonatal seizures caused by stroke. A systematic review - Sortino, Vincenzo; Praticò, Andrea; Marino, Silvia; Criscione, Roberta; Ruggieri, Martino; Pisani, Francesco; Falsaperla, Raffaele (Acta Biomedica Atenei Parmensis, 2022)
Background and aim. Neonatal stroke is the second cause of acute symptomatic neonatal seizures after hypoxic-ischemic encephalopathy. The aim of this systematic review is to determine which drug among those available represents the best therapeutic choice for treatment of secondary seizures due to neonatal stroke.Methods. We performed a systematic review searching on PubMed the keywords “Neonatal”, “Stroke”, “Seizures” and “Treatment”. Search was limited only to English language with no time limit. Last literature search was done on May 30, 2022.Results. We selected 5 articles involving a total of 52 full-term neonates. In 96.1% the first line treatment was phenobarbital and in 3.9% was used phenobarbital associated with midazolam from the seizure onset but in all of these cases it was necessary to introduce further medications for controlling the seizures. As second line treatment was used lidocaine (response rate of 53.3%), midazolam (response rate of 15.38%) bumetanide (response rate of 100%), and fosphenytoin (no response). As third line treatment was used lidocaine (response rate of 87.5%), Midazolam (response rate of 60%), levetiracetam and clonazepam (response rate of 100%).Conclusions. Our review shows that the use of ASMs that act throughout a gabaergic mechanism are inadequate in controlling seizures secondary to neonatal stroke in full-term newborns. Very effective seems to be lidocaine and levetiracetam with an apparent safer profile in short and long term. Bumetanide shows promising results, but they need to be confirmed by phase 3 studies.